Traceability information model for very small entities with ISO/IEC 29110 - Carrión M.A.G. (2018)
The authors would like to thank CONCYTEC (Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica), FONDECYT (Fondo Nacional de Desarrollo Científico y Tecnológico) for supporting this project and also Ph.D. Jose Antonio Pow-Sang for his interest in the project.